Biomechanical improvements following foot strike biofeedback training for a patient using a passive dynamic ankle-foot orthosis during running. (August 2019) - Yoder, Adam J; Mazzone, Brittney N; Miltenberger, Richard S; Farrokhi, Shawn
Background and Purpose: Passive dynamic ankle-foot orthoses have potential to facilitate return to running after a lower limb trauma. However, transitioning patients to new movement patterns that enhance passive dynamic ankle-foot orthoses benefits can pose a challenge. The purpose of this case study was to report biomechanical and functional outcomes for a patient utilizing a passive dynamic ankle-foot orthoses following completion of a session-based, midfoot strike run training program. Case Description and Methods: A patient using a passive dynamic ankle-foot orthoses to run due to surgically reconstructed tibiafracture underwent eight treadmill running sessions over 2 weeks while viewing continuous visual feedback on measured foot strike. Findings and Outcomes: After treatment, foot strike was changed from rearfoot to midfoot on the affected limb along with an 18% increase in mechanical work ratio of the ankle-foot-brace complex. Similar improvements were retained at one and five months following treatment. Conclusion: This report provides preliminary evidence that biofeedback-based foot strike training can enhance ankle-foot mechanical performance of patients using a passive dynamic ankle-foot orthoses to run. Clinical relevance: For patients using a passive dynamic ankle-foot orthoses to run following lower limb trauma, supplementing standard rehabilitation programs with biofeedback-based footstrike training may improve biomechanical performance and running capability.